2011
DOI: 10.1007/s00103-011-1316-z
|View full text |Cite
|
Sign up to set email alerts
|

Altersbilder im Bereich der gesundheitlichen Versorgung älterer Menschen

Abstract: This paper is based on the Sixth National Social Report on the Situation of the Elderly, published in November 2010, that deals with the images of aging that exist in society. The aim of this paper is to describe how the commission that wrote the Sixth National Social Report on the Situation of the Elderly evaluates the role of images of aging in the field of health care and to specify the need for change that the commission identifies with respect to images of aging. The paper consists of four parts. A genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…He described ageing with changes, which can be perceived as gain and as loss. In addition, he mentions a possible influence of the negative experiences of students occurring in the health care sector in the context of their education on their attitudes towards seniors [ 42 ]. If the attitude of the medical students summarized by Berner is compared with the results of this study, this negative development of the attitude towards seniors cannot be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…He described ageing with changes, which can be perceived as gain and as loss. In addition, he mentions a possible influence of the negative experiences of students occurring in the health care sector in the context of their education on their attitudes towards seniors [ 42 ]. If the attitude of the medical students summarized by Berner is compared with the results of this study, this negative development of the attitude towards seniors cannot be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing life expectancy and a higher level of prosperity have resulted in a social change of old age as a stage of life. This led to the concept of the so-called 'new elderly' , who still have many years to live after reaching the seventh decade and whose health and socioeconomic situation allows them to organise these years according to their own interests and to realise some individual ambitions [6]. As ageing perceptions have changed, health-related behaviours (e.g., physical activity or use of preventive services) have also changed, but this again depends on the education level and in some cases, on sex [7].…”
Section: Introductionmentioning
confidence: 99%